Management of a patient with multiple device replacements and extractions: When the leadless pacemaker is a viable solution. Issue 3 (9th November 2022) - Coppola, Giuseppe; Ciaramitaro, Gianfranco; Madaudo, Cristina; Di Caccamo, Leandro; Testa, Gabriella; Castelluccio, Emanuele; Rizzuti, Guglielmo; Torre, Salvatore; Novo, Giuseppina; Galassi, Alfredo Ruggero; Corrado, Egle
Abstract: Leadless pacemaker (LPs) is a safe device and the implantation rates of this device is increasing. The device extraction and replacement are today a challenging procedures especially in case of infections, fragile and older patients or in unfavorable venous anatomy; LPs can be a valid alternative strategy in these cases. We report a case of management of a patient with multiple previous device replacements and extractions, with malfunction of transvenous pacemaker and with a fibrous membrane between the walls of the ventricular lead and the superior vena cava (SVC), who underwent a successful LP implantation.